ISOLATION, IDENTIFICATION, AND ANTIBIOTIC SENSITIVITY AGAINST Salmonella sp. FROM HATCHERY KUB CHICKEN IN YOGYAKARTA [Isolasi, Identifikasi, dan Sensitivitas Antibiotik Terhadap Salmonella sp. dari Penetasan Ayam KUB di Yogyakarta] - Suwito, Widodo; Setya Adji, Rahmat; Faiz Karimy, Moh. (BRIN Publishing (Penerbit BRIN), 2023)
Salmonella sp. is responsible bacteria that causes salmonellosis in hatchery-produced local chicken (KUB) in Yogyakarta. The objective of this study was to determine of character Salmonella sp. from hatchery KUB chicken in Yogyakarta. This study was carried out in KUB chicken hatcheries in Yogyakarta province, specifically in the Sleman district (n = 5), Bantul (n = 3), Kulonprogo (n = 3), and Gunungkidul (n=2). Isolation and identification of Salmonella sp. were done from eggshells (n=17) and chick fluff of KUB chicken (n = 13) based on conventional methods with the bacteriological analytical manual (BAM). Sensitivity of Salmonella sp. against antibiotics is determined by antimicrobial diffusion agar with a paper disc antibiotic. A total of 3 isolates of Salmonella sp. were isolated from eggshells (n=2) and chick fluff from KUB chicken (n=1). Salmonella sp. was sensitive to tetracycline, oxytetracycline, enrofloxacin, sulfamethoxazole and resistant to ampicillin and erythromycin. The study showed that the hatchery of KUB chicken in Yogyakarta was contaminated with Salmonella sp. and had resistance to several antibiotics. Therefore, desinfection in incubator hatcheries using KUB chicken should continue after the egg hatches.